2018
DOI: 10.12681/jhvms.16430
|View full text |Cite
|
Sign up to set email alerts
|

Welfare parameters in dairy cows reared in tie-stall and open-stall farming systems: pilot study

Abstract: ABSTRACT. Animals can experience pain or distress as a result of widely accepted management practices. In dairy cattle, housing system can affect animal welfare. The assessment of animal welfare requires the use of multiple indicators in order to analyse the heterogeneity of the aspects involved. The aim of this study was to compare the welfare of dairy cows reared in a tie-stall (TS) and open-stall (OS) system by metabolic, immunological and stress related parameters. The study involved 80 pluriparous lactati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…High plasma NEFA levels with other parameters such as BHBA and OFR (Herdt, 2000) could be indices of inflammation. In our study, no critical situation regarding these parameters was shown (Table 3) (Giuliotti et al, 2017;Benvenuti et al, 2018). In fact, although NEFA was far below the normal threshold, Cozzi et al (2011) reported that in mid-lactation NEFA concentration decreases when the energy balance turns positive; in any case, Oetzel (2004) reported that low NEFA concentrations are not biologically important.…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…High plasma NEFA levels with other parameters such as BHBA and OFR (Herdt, 2000) could be indices of inflammation. In our study, no critical situation regarding these parameters was shown (Table 3) (Giuliotti et al, 2017;Benvenuti et al, 2018). In fact, although NEFA was far below the normal threshold, Cozzi et al (2011) reported that in mid-lactation NEFA concentration decreases when the energy balance turns positive; in any case, Oetzel (2004) reported that low NEFA concentrations are not biologically important.…”
Section: Resultsmentioning
confidence: 47%
“…Del Rosario et al ( 2011) reported hair cortisol concentrations equal to 12.15 ± 1.85 pg mg −1 in 2-year-old cows, and Burnett et al (2014) found a cortisol level equal to 11.0 ± 1.2 pg mg −1 in lactating dairy cows. Benvenuti et al (2018) observed higher values in dairy cows reared in an open-stall system.…”
Section: Resultsmentioning
confidence: 75%
“…No official national statistics or reports could be accessed on dairy cow husbandry in Italy. However, scientific literature illustrates that farm structure, housing systems, and the extent of access to pasture for dairy cows differ considerably between regions in Italy (Benvenuti et al., 2018 ; Lora et al., 2020 ; Peli et al., 2016 ; Pugliese et al., 2021 ; Tarantola et al., 2016 ).…”
Section: Appendix C – Dairy Husbandry Systems: Distribution In the Ma...mentioning
confidence: 99%
“…In the Alpine region, including e.g. Mugello (Benvenuti et al., 2018 ) or Piedmont region (Tarantola et al., 2016 ), with a high percentage of small‐scale farms, structural and economic constraints, tie‐stalls are the most prevalent housing system. In 2005, tie‐stall systems still represented more than 98% of the total barns in the Alpine region (ISTAT in: Corazzin et al., 2010 ).…”
Section: Appendix C – Dairy Husbandry Systems: Distribution In the Ma...mentioning
confidence: 99%
“…An increase in the number of farm animals is associated with the complexities of management and veterinary care, and the deterioration of their health (Barkema et al 2015;Murray et al 2015;Wolf et al 2016;Song et al 2018). Obviously for this reason, as well as due to over-intensive exploitation, their morbidity and decrease in the productive longevity of dairy cows is occur (Curone et al 2018;Benvenuti et al 2018).…”
Section: Introductionmentioning
confidence: 99%